Створення й використання бази даних складів англійського мовлення для блоку лінгвістичної обробки текстів у системі конкатенативного синтезу - Володкевич, О. (Лексикографічний бюлетень, 2006)
The article focuses on the problem of English speech synthesis in the System of Concatenation Synthesis. The core principles and difficulties in creating the database for the synthesis are under our analysis. The article presents the structure of the database and the corresponding concepts of its usage in the application. The database strategies underline the natural sounding of the synthesized speech and saving the individual features of a Speaker.